Analysis of shear forces during mash disk formation - Allwright, David (2020)
This report concerns a forming process in which mash is forced from a spreading manifold into moulds on a rotating drum, transported in the moulds underneath a surface held flush with the drum (the shoe), and ejected from the moulds. The quality of the final product is understood to be related to the shear stresses experienced by the mash in the moulds as it is transported under the shoe. We describe and analyse mathematical models of the forming process, focusing on the fluid mechanics of mash in a mould. We treat this as a driven cavity flow and obtain flow profiles, stress profiles, and expressions for the maximum shear stress for different rheological models of the mash (Newtonian fluid, power-law fluid, and Bingham plastic).